(untitled) (Acta Scientiarum. Health Sciences, 2017)
The use of novel drugs such as inhaled loxapine (LOXi) for schizophrenia and the off-label use of substances such as sodium nitroprusside (NIT) for the management of mental disorders require further investigation. We aimed to evaluate the efficacy and safety of LOXi and NIT for the treatment of agitation associated with schizophrenia. A systematic review of randomized controlled trials (RCTs) comparing the use of LOXi or NIT versus placebo or other antipsychotic agents was conducted, and we evaluated the efficacy (CGI-scale) and safety (adverse events) of the therapies. Altogether, 71 studies were identified, of which 2 (LOXi) were included in the meta-analysis, and 1 (NIT) was included in the systematic review only. The efficacy data showed superiority of LOXi against placebo, regardless of the dose (5 and 10 mg). No significant differences were observed concerning the safety results. Treatment with NIT showed favorable results, with significant reduction of the symptoms. The efficacy of these medications is difficult to assess because of the lack of RCTs. However, there is some information regarding the efficacy and safety of LOXi in the treatment of agitation in schizophrenic patients.